Psychosocial predictors of mammography history among Chinese American women without a recent mammogram. Issue 6 (17th August 2020) - Miller, Brittany C.; Sarma, Elizabeth A.; Sun, Yiyuan; Messina, Catherine R.; Moyer, Anne
ABSTRACT: Chinese American women have lower rates of mammography screening compared with non-Hispanic White women. Although the extent of perceived barriers, as conceptualized by the Health Belief Model, have been shown to distinguish between currently non-adherent Chinese American women who have ever and never had a mammogram, it is less clear which types of perceived barriers differentiate them. One hundred twenty-eight Chinese American women in the New York metropolitan area who had not had a mammogram in the past year completed baseline assessments for a mammography framing intervention study. Demographics, medical access variables, and perceived barriers to mammography (lack of access, lack of need for screening, and modesty) were used to predict mammography history (ever versus never screened). Fifty-five women (43%) reported having been screened at least once. A sequential logistic regression showed that English speaking ability and having health insurance significantly predicted mammography history. However, these control variables became non-significant when the three barrier factors were included in the final model. Women who reported a greater lack of access ( OR = 0.36, p < .05) and greater lack of need ( OR = 0.27, p < .01) were less likely to be ever screeners. Unexpectedly, women who reported greater modesty were more likely to be ever screeners ( OR = 4.78, p < .001). The results suggest that interventions for Chinese American women should identify and target specific perceived barriers with consideration of previous adherence.